2007
DOI: 10.1074/jbc.m702975200
|View full text |Cite
|
Sign up to set email alerts
|

The Calponin Homology Domain of Vav1 Associates with Calmodulin and Is Prerequisite to T Cell Antigen Receptor-induced Calcium Release in Jurkat T Lymphocytes

Abstract: Vav1 is a guanine nucleotide exchange factor that is expressed specifically in hematopoietic cells and plays important roles in T cell development and activation. Vav1 consists of multiple structural domains so as to facilitate both its guanine nucleotide exchange activity and scaffold function following T cell antigen receptor ( Stimulation of the T cell antigen receptor (TCR)2 initiates a cascade of signaling events that lead to T cell activation. Calcium plays a central role in this process and has been st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 58 publications
4
28
0
Order By: Relevance
“…1C). These results are consistent with previously reported findings (52). It has also been reported that PLC␥1 phosphorylation is not significantly altered by oncoVav1 expression (52).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…1C). These results are consistent with previously reported findings (52). It has also been reported that PLC␥1 phosphorylation is not significantly altered by oncoVav1 expression (52).…”
Section: Discussionsupporting
confidence: 83%
“…These results are consistent with previously reported findings (52). It has also been reported that PLC␥1 phosphorylation is not significantly altered by oncoVav1 expression (52). However, our results indicate that the TCR-induced phosphorylation of the critical Tyr-783 residue of PLC␥1 is diminished in cells expressing oncoVav1 compared with cells expressing WT Vav1 (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We previously reported that the CH domain was indispensable for Vav1-CaM interaction, and that the complex potentiated calcium release in a GEF-independent manner (11). However, the precise role of Vav1 that is different from other Vav proteins still remains to be investigated.…”
Section: Vav1 Is a Guanine Nucleotide Exchange Factor (Gef)mentioning
confidence: 99%
“…Plasmid DNA Constructs-The plasmids encoding Vav1 and the CH-truncated mutation, Vav1⌬CH, were prepared in our laboratory as described (11). Other constructs for the expression of N-terminal-truncated mutants of Vav1 were derived from plasmid encoding wild type Vav1 by polymerase chain reactions (PCR) with the corresponding oligonucleotides, and the mutant fragments were subcloned into pcDNA4/HisMax.C vector at BamHI and XhoI restriction sites.…”
Section: Methodsmentioning
confidence: 99%